Highly corrosion-resistant zinc-magnesium alloy plated steel sheet and production process thereof
Patent Information
- Application Number
- CN202611251135.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-18
- Publication Date
- 2026-10-09
AI Technical Summary
本发明通过构建“Fe-Zn-Mg三元合金内层+Zn-Mg共晶外层”的双层镀层结构,从根本上解决了传统镀锌层在含氯腐蚀环境中屏蔽保护与牺牲保护无法协同兼顾的根本矛盾。Zn-Mg共晶外层在腐蚀过程中引导生成致密保护膜,有效封堵侵蚀通道;三元合金内层因镁固溶获得牺牲阳极活性,且结构致密,在镀层破损或切边暴露时,能以缓慢均匀的消耗为钢基体提供长效电化学保护,显著提升镀层的耐腐蚀寿命与切边保护能力。
Abstract
Description
Technical Field
[0001] This invention relates to the field of metal materials technology, specifically to a high corrosion-resistant zinc-magnesium alloy coated steel sheet and its production process. Background Technology
[0002] Steel materials are widely used in construction, automobiles, machinery manufacturing, marine engineering, and many other fields, but corrosion remains a key factor limiting service life and increasing maintenance costs. Hot-dip galvanizing is one of the most economical and effective methods for steel corrosion protection, its principle being to rely on the zinc coating to provide sacrificial anode protection to the steel substrate.
[0003] However, in harsh corrosive environments containing chloride ions (such as marine climates, industrial acid rain, and road de-icing salt), the protective life of traditional hot-dip galvanized coatings is significantly shortened. This is because traditional galvanized coatings face a dual challenge in such environments: Firstly, the corrosion products, under the action of chloride ions, have a loose and porous structure, which cannot effectively block the continuous intrusion of corrosive media, leading to the rapid consumption of the zinc layer. The products generated after the corrosion of traditional zinc plating layers (such as zinc hydroxide and basic zinc carbonate) are difficult to form a dense barrier layer in a chloride ion environment. Instead, they adhere to the surface in a loose state, allowing external water, oxygen, and chloride ions to continuously penetrate. The zinc layer continues to dissolve at a high rate and is eventually depleted prematurely.
[0004] Secondly, under suitable conditions, an excessively dense product film may form on the surface of a traditional galvanized layer. While this film acts as a physical barrier, it excessively inhibits the anodic dissolution reaction of zinc. Since sacrificial anode protection requires zinc to maintain a certain active dissolution rate to provide protective current to the exposed steel substrate (such as cut edges, scratches, and other damaged areas), once the dissolution of zinc is excessively inhibited by the dense product film, the sacrificial protection effect is interrupted, leading to preferential corrosion at cut edges and damaged areas.
[0005] The aforementioned dual dilemmas actually point to the same fundamental contradiction: traditional galvanized coatings cannot achieve a synergistic balance between "effectively shielding against external corrosion" and "continuously providing sacrificial protection"—a loose product film provides insufficient shielding, while a dense product film inhibits sacrificial reactions. Simultaneously, in exposed steel substrate areas without coating coverage, such as cut edges, traditional galvanized coatings lack a long-term electrochemical protection mechanism.
[0006] To improve the corrosion resistance of galvanized coatings, the industry has developed zinc-aluminum-magnesium coatings with higher aluminum content. However, the high aluminum and magnesium content in these coatings can easily lead to increased slag formation in the plating solution and reduced weldability of the coating. Furthermore, they can easily generate harmful phases during the production process that cause surface discoloration and localized preferential corrosion, limiting their application in fields with high appearance requirements.
[0007] Therefore, there is an urgent need for a solution that can overcome the above-mentioned problems and achieve stable mass production of high corrosion-resistant coated steel sheets. Summary of the Invention To address the aforementioned technical problems, the present invention aims to provide a high corrosion-resistant zinc-magnesium alloy coated steel sheet and its manufacturing process. This invention, by constructing a double-layer coating structure of "Fe-Zn-Mg ternary alloy inner layer + Zn-Mg eutectic outer layer," fundamentally solves the contradiction that traditional zinc coatings cannot simultaneously achieve shielding and sacrificial protection in chlorine-containing environments, significantly improving corrosion resistance lifespan and edge protection capabilities.
[0008] To achieve the above-mentioned technical objectives and effects, the present invention is implemented through the following technical solution: This invention provides a high corrosion-resistant zinc-magnesium alloy coated steel sheet, comprising a steel substrate and a hot-dip alloy coating. The hot-dip alloy coating includes an inner Fe-Zn-Mg ternary alloy layer covering the surface of the steel substrate, and an outer Zn-Mg eutectic layer covering the inner ternary alloy layer. The microstructure of the Zn-Mg eutectic outer layer includes a eutectic structure composed of η-Zn phase and MgZn2 phase.
[0009] In a preferred embodiment, the Zn-Mg eutectic outer layer contains 0.02% to 0.06% Mg by mass percentage, with the balance being Zn and unavoidable impurities; The thickness of the Fe-Zn-Mg ternary alloy inner layer is 1–5 μm.
[0010] Furthermore, the inner layer of the Fe-Zn-Mg ternary alloy has an equiaxed or fine-grained structure with an average grain size of less than 2 μm, and the Mg content in the inner layer of the ternary alloy increases from the steel matrix side to the eutectic outer layer side along the thickness direction.
[0011] Furthermore, the MgZn2 phase in the Zn-Mg eutectic outer layer is uniformly distributed in the η-Zn matrix in a dispersed granular or short rod-shaped morphology, and the average particle size of the MgZn2 phase does not exceed 3 μm.
[0012] Furthermore, between the Fe-Zn-Mg ternary alloy inner layer and the steel substrate, there is a discontinuous Al-containing interface layer. This Al-containing interface layer contains Fe-Al intermetallic compounds and has a thickness of 0.02–0.3 μm. Moreover, this Al-containing interface layer is partially penetrated or replaced by the Fe-Zn-Mg ternary alloy inner layer over at least 50% of its area.
[0013] Furthermore, the total thickness of the hot-dip alloy coating is 10–30 μm, and the thickness of the Zn-Mg eutectic outer layer accounts for more than 70% of the total coating thickness (Zn and Mg elements are uniformly distributed).
[0014] Another aspect of the present invention provides a method for preparing a high corrosion-resistant zinc-magnesium alloy coated steel sheet, comprising continuous annealing, hot-dip galvanizing, and cooling of a cold-rolled steel strip, wherein the hot-dip galvanizing step uses a zinc-based alloy bath containing at least Mg and Zn; the galvanizing temperature is 440–480°C, and the galvanizing time is 2–6 seconds; after the steel strip exits the bath, it is forcibly cooled to below 400°C at a cooling rate of 10–40°C / s.
[0015] Furthermore, the forced cooling is implemented in stages: after the steel strip is removed from the bath and purged with an air knife, it is immediately subjected to rapid cooling at a rate of 10-40°C / s. When the surface temperature of the coating drops to 390-400°C, it enters a slow cooling stage with a cooling rate not exceeding 6°C / s.
[0016] Furthermore, the zinc-based alloy bath contains 0.02% to 0.20% Mg; the zinc-based alloy bath also contains Al, with an Al content of 0.35% to 0.60%, and an Al / Mg mass ratio of 1.5 to 2.5.
[0017] Furthermore, in the zinc-based alloy bath at the immersion temperature, Mg and Al first form Mg-Al intermetallic compound particles, which adhere to the surface of the steel strip along with the zinc liquid. During the subsequent cooling process, Mg atoms are decomposed and released, participating in the Zn-Mg eutectic reaction and the formation of the Fe-Zn-Mg ternary alloy inner layer. In the initial stage of immersion plating, Al reacts with the steel substrate to form an Al-containing interface barrier layer. In the later stage of immersion plating, this barrier layer is at least partially dissolved in the zinc-based alloy bath, exposing the iron covered by it. The exposed iron reacts with Zn in the zinc-based alloy bath and Mg released from Mg-Al intermetallic compound particles to generate the Fe-Zn-Mg ternary alloy inner layer in situ.
[0018] The beneficial effects of this invention are as follows: This invention fundamentally solves the inherent contradiction of traditional zinc plating layers in achieving both shielding and sacrificial protection in chlorine-containing corrosive environments by constructing a double-layer coating structure of "Fe-Zn-Mg ternary alloy inner layer + Zn-Mg eutectic outer layer". The Zn-Mg eutectic outer layer guides the formation of a dense protective film during corrosion, effectively blocking corrosion pathways. The ternary alloy inner layer, due to magnesium solid solution, acquires sacrificial anodic activity and has a dense structure. When the coating is damaged or the cut edges are exposed, it can provide long-term electrochemical protection to the steel substrate through slow and uniform consumption, significantly improving the coating's corrosion resistance and edge protection capabilities.
[0019] At the microstructure level, the inner layer of the ternary alloy exhibits an equiaxed fine-grained structure, which avoids the formation of brittle columnar iron-zinc phases in traditional hot-dip galvanizing and fundamentally improves the processing and forming performance of the coating. The MgZn2 phase is uniformly dispersed in the eutectic outer layer, ensuring the uniformity and density of the corrosion product film.
[0020] At the manufacturing method level, the aforementioned microstructure can be stably obtained through segmented cooling and synergistic control of the zinc bath composition. This involves a cooling regime of rapid cooling for shaping followed by slow cooling to release stress after hot-dip plating. The process window is wide and suitable for continuous mass production. In particular, the formation of a Mg-Al protective carrier by controlling the Al / Mg ratio in the zinc bath effectively suppresses the oxidation and burn-off of magnesium, overcoming the industrial bottleneck of the difficulty in stably adding trace amounts of magnesium during hot-dip plating. Detailed Implementation
[0021] The technical solutions of the present invention will be clearly and completely described below with reference to specific embodiments. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0022] This invention provides a high corrosion-resistant zinc-magnesium alloy coated steel sheet, comprising a steel substrate and a hot-dip alloy coating. The hot-dip alloy coating includes an inner Fe-Zn-Mg ternary alloy layer covering the surface of the steel substrate, and an outer Zn-Mg eutectic layer covering the inner ternary alloy layer. This dual-layer structure fundamentally solves the contradiction between shielding protection and sacrificial protection in traditional zinc coatings in chlorine-containing environments, enabling the steel sheet of this invention to possess both excellent corrosion resistance and edge protection capabilities.
[0023] The microstructure of the aforementioned Zn-Mg eutectic outer layer comprises a eutectic structure consisting of the η-Zn phase and the MgZn2 phase. The η-Zn phase forms a continuous substrate, while the MgZn2 phase is dispersed within it. In the early stages of corrosion, the MgZn2 phase in the outer layer preferentially dissolves and releases magnesium ions, guiding the formation of a dense protective film on the surface, primarily composed of zinc ore. This effectively seals corrosion channels and blocks external corrosive media. Simultaneously, the η-Zn phase, as the main phase, provides basic sacrificial anodic protection. Through this synergistic effect, the corrosion resistance of the outer layer is significantly improved compared to traditional pure zinc plating.
[0024] The Zn-Mg eutectic outer layer contains 0.02% to 0.06% Mg by mass, with the balance being Zn and unavoidable impurities. Controlling the Mg content within this range allows magnesium to fully guide the formation of a dense protective film while preventing the formation of harmful Zn due to excessive Mg content. 11 The Mg2 phase ensures the appearance quality and corrosion resistance uniformity of the coating surface.
[0025] Preferably, the total thickness of the hot-dip alloy coating is 10–30 μm, and the thickness of the Zn-Mg eutectic outer layer accounts for more than 70% of the total coating thickness. Preferably, the thickness of the Fe-Zn-Mg ternary alloy inner layer is 1–5 μm. When the thickness of the ternary alloy inner layer is within the above range, it can provide sufficient physical barrier effect and sacrificial anode protection capacity, while avoiding brittleness due to excessive thickness, so that the coating has good adhesion and crack resistance during bending, stamping and other processing.
[0026] More preferably, the Fe-Zn-Mg ternary alloy inner layer has an equiaxed or fine-grained structure with an average grain size of less than 2 μm. Unlike traditional brittle columnar iron-zinc intermetallic compound layers such as δ-phase and ζ-phase, the equiaxed fine-grained structure eliminates directionality, allowing corrosion to propagate uniformly along grain boundaries rather than selectively and rapidly penetrating. This significantly reduces the consumption rate of the inner layer while maintaining sacrificial protection activity, achieving long-term protection. Furthermore, the Mg content in the ternary alloy inner layer increases progressively along the thickness direction from the steel substrate side to the eutectic outer layer side. Specifically, the Mg content is lower near the steel substrate side, ensuring good adhesion and toughness; the Mg content is higher near the eutectic outer layer side, resulting in stronger electrochemical activity and providing more effective sacrificial protection at damaged or cut edges. This gradient distribution allows for a smooth transition between the mechanical and electrochemical protective properties of the coating along the thickness direction, avoiding abrupt performance changes at the interface.
[0027] More preferably, the MgZn2 phase in the Zn-Mg eutectic outer layer is uniformly distributed in the n-Zn matrix in a dispersed granular or short rod-like morphology, with an average particle size of no more than 3 μm. The MgZn2 phase is a key functional phase that guides the formation of the protective film. Its uniform dispersion facilitates the uniform release of magnesium ions during corrosion, thereby forming a continuous and dense protective film. Conversely, if MgZn2 agglomerates in coarse, blocky forms, it will lead to localized preferential corrosion and surface discoloration. Controlling the particle size within the above range balances corrosion resistance and surface appearance.
[0028] In a preferred embodiment, a discontinuous Al-containing interface layer exists between the Fe-Zn-Mg ternary alloy inner layer and the steel substrate. This Al-containing interface layer contains Fe-Al intermetallic compounds, has a thickness of 0.02–0.3 μm, and is partially penetrated or replaced by the Fe-Zn-Mg ternary alloy inner layer over at least 50% of its area. This interface layer is formed initially by the reaction of Al with the steel substrate during hot-dip galvanizing, and then partially dissolves in the zinc-based alloy bath in the later stages of galvanizing, exposing the iron covered by it. The exposed iron can react with zinc and magnesium to form the ternary alloy inner layer in situ. After cooling, the undissolved portion remains at the interface in a discontinuous island or granular form. The advantages of this structure are: the ternary alloy inner layer is directly metallurgically bonded to the steel substrate over a large area, ensuring strong adhesion; while the residual Al-containing interface layer acts as an auxiliary barrier, further improving the corrosion resistance reliability of the interface.
[0029] The present invention also provides a method for manufacturing the above-mentioned high corrosion-resistant zinc-magnesium alloy coated steel sheet, the process route of which is: continuous annealing of cold-rolled steel strip → hot-dip coating → cooling.
[0030] Specifically, the hot-dip galvanizing step uses a zinc-based alloy bath containing at least Mg and Zn. By controlling the Mg content within a certain range, the desired double-layer coating structure can be formed on the steel strip surface. Typically, the immersion temperature is 440–480°C, and the immersion time is 2–6 seconds. Within this temperature and time window, the zinc bath has moderate fluidity, ensuring uniform coating coverage while avoiding excessive growth of brittle interfacial phases. After immersion, the steel strip is removed from the bath and forced to cool to below 400°C at a cooling rate of 10–40°C / s. Rapid cooling causes the outer layer of the coating to solidify quickly, forming a fine Zn-Mg eutectic structure, preventing excessive coarsening of the MgZn2 phase, and simultaneously promoting the densification of the Fe-Zn-Mg ternary alloy inner layer.
[0031] More preferably, the forced cooling is implemented in stages: after the steel strip is removed from the bath and purged with an air knife, it is immediately rapidly cooled at a rate of 10–40°C / s. When the surface temperature of the coating drops to 390–400°C, the outer eutectic structure has basically solidified and set. Subsequently, a slow cooling stage with a cooling rate not exceeding 6°C / s is adopted to allow the interior of the coating to complete final solidification and relax thermal stress. Through this staged cooling system of "rapid cooling for setting + slow cooling for stress relief," precise control of the coating's microstructure can be achieved without adding any additional equipment, while avoiding microcracks caused by thermal stress concentration, ensuring the integrity and processing performance of the coating.
[0032] In a more preferred process, the zinc-based alloy bath contains 0.02%–0.20% Mg and 0.35%–0.60% Al, with an Al / Mg mass ratio of 1.5–2.5. For example, using a zinc-based alloy bath with 0.18% Mg and 0.45% Al, the Al / Mg ratio is approximately 2.25. At this ratio, at the immersion temperature, Mg and Al preferentially form fine Mg-Al intermetallic compound particles. These particles are encapsulated by an aluminum oxide film and stably suspended in the zinc bath, effectively suppressing magnesium oxidation and burn-off. During immersion plating, these particles adhere to the steel strip surface along with the zinc bath; during subsequent cooling, the Mg-Al particles decompose and release Mg atoms. Some of the released Mg atoms participate in the Zn-Mg eutectic reaction, generating a uniform and fine eutectic structure on the outer layer of the coating, while others diffuse towards the steel substrate, participating in the formation of the Fe-Zn-Mg ternary alloy inner layer. Simultaneously, in the initial stage of immersion plating, Al reacts first with the steel substrate, forming a continuous Al-containing interfacial barrier layer at the interface. This barrier layer dissolves at least partially in the zinc-based alloy bath in the later stage of immersion plating, exposing the underlying iron. The exposed iron then reacts with Zn in the zinc-based alloy bath and Mg released from Mg-Al particles, forming the Fe-Zn-Mg ternary alloy inner layer in situ. After the reaction is complete, the undissolved barrier layer remains as a discontinuous Fe-Al intermetallic compound between the ternary alloy inner layer and the steel substrate. This mechanism allows for precise control of the previously difficult-to-control hot-dip plating process, significantly improving the effective utilization rate of magnesium and maintaining a stable plating bath composition, thereby ensuring a high yield of the target double-layer plating structure in continuous production.
[0033] Example 1
[0034] Hot-rolled pickled steel coils with a thickness of 2.0 mm were selected and cold-rolled to a thickness of 0.8 mm into cold-rolled steel strip. The steel strip underwent recrystallization annealing at 750°C in a continuous annealing furnace under a nitrogen-hydrogen mixture atmosphere. After annealing, the steel strip was hot-dip coated in a zinc-based alloy bath. The composition of the zinc-based alloy bath was: 0.18% Mg, 0.45% Al, with the balance being Zn and unavoidable impurities. The bath temperature was 455°C, and the immersion time was 4 seconds. After exiting the bath, the steel strip was purged with an air knife and then rapidly cooled to approximately 390°C at a cooling rate of approximately 15°C / s. It was then subjected to natural slow cooling at a rate of approximately 3°C / s until it reached room temperature, after which it was coiled. The resulting coating thickness is approximately 18 μm. Cross-sectional metallographic observation shows that the inner layer of the Fe-Zn-Mg ternary alloy is approximately 2.5 μm thick, exhibiting an equiaxed fine-grained structure. The outer layer is a dispersed eutectic structure of η-Zn phase and MgZn2 phase, with an average MgZn2 phase grain size of approximately 1.8 μm and an outer layer Mg content of approximately 0.05%. Neutral salt spray testing (ISO 9227) showed that the time to the appearance of red rust exceeded 1800 hours, while that of conventional galvanized sheets of the same thickness was 360 hours. In cyclic corrosion testing (CCT) with cut edges, the maximum corrosion penetration width at the cut edge was only 1.5 mm after 8 weeks, compared to 4.2 mm for conventional galvanized sheets of the same thickness.
[0035] Example 2
[0036] Hot-rolled pickled steel coils with a thickness of 3.0 mm were selected and cold-rolled to a thickness of 1.2 mm into cold-rolled steel strip. The steel strip underwent recrystallization annealing at 780℃ in a continuous annealing furnace under a nitrogen-hydrogen mixture atmosphere. After annealing, the steel strip was hot-dip coated in a zinc-based alloy bath. The composition of the zinc-based alloy bath was: 0.10% Mg, 0.38% Al, with the balance being Zn and unavoidable impurities. The bath temperature was 465℃, and the immersion time was 3 seconds. After exiting the bath, the steel strip was purged with an air knife and rapidly cooled to approximately 390℃ at a cooling rate of approximately 20℃ / s. It was then transferred to a slow cooling section at a slow cooling rate of approximately 4℃ / s and cooled to room temperature before being coiled. The resulting coating thickness was approximately 15 μm. Cross-sectional metallographic observation showed that the inner layer of the Fe-Zn-Mg ternary alloy was approximately 1.8 μm thick, with a fine-grained structure. The outer MgZn2 phase was uniformly dispersed, and the Mg content in the outer layer was approximately 0.03%. The neutral salt spray test takes more than 1,500 hours to produce red rust, while the traditional galvanized sheet of the same thickness takes 360 hours.
[0037] Example 3
[0038] Hot-rolled pickled steel coils with a thickness of 2.5 mm were selected and cold-rolled to a cold-rolled steel strip with a thickness of 1.0 mm. The steel strip was recrystallized and annealed in a continuous annealing furnace at 760℃ in a nitrogen-hydrogen mixture atmosphere. After annealing, the steel strip was hot-dip coated in a zinc-based alloy bath. The composition of the zinc-based alloy bath was: 0.08% Mg, 0.50% Al, with the balance being Zn and unavoidable impurities. The bath temperature was 450℃, and the immersion time was 5 seconds. After exiting the bath, the steel strip was purged with an air knife and rapidly cooled to approximately 395℃ at a cooling rate of approximately 12℃ / s. It was then transferred to a slow cooling section at a slow cooling rate of approximately 2.5℃ / s and cooled to room temperature before being coiled. The resulting coating thickness was approximately 22 μm. Cross-sectional metallographic observation showed that the inner layer of the Fe-Zn-Mg ternary alloy was approximately 3.0 μm thick, exhibiting an equiaxed fine-grained structure, while the outer MgZn2 phase was uniformly dispersed, with an outer Mg content of approximately 0.02%. The neutral salt spray test takes more than 1300 hours to reach red rust, and the maximum penetration width of the cut edge cyclic corrosion after 8 weeks is only 2.0 mm, while that of traditional galvanized sheet of the same thickness is 4.2 mm.
[0039] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the invention can be implemented in other specific forms without departing from the spirit or essential characteristics of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description. Thus, it is intended that all variations falling within the meaning and scope of equivalents of the claims be included within the present invention.
[0040] Furthermore, it should be understood that although this specification describes embodiments, not every embodiment contains only one independent technical solution. This narrative style is merely for clarity. Those skilled in the art should consider the specification as a whole, and the technical solutions in each embodiment can also be appropriately combined to form other embodiments that can be understood by those skilled in the art.
Claims
1. A high corrosion-resistant zinc-magnesium alloy coated steel sheet, comprising a steel substrate and a hot-dip alloy coating, characterized in that, The hot-dip alloy coating includes an inner Fe-Zn-Mg ternary alloy layer covering the surface of the steel substrate, and an outer Zn-Mg eutectic layer covering the inner ternary alloy layer. The microstructure of the Zn-Mg eutectic outer layer includes a eutectic structure composed of η-Zn phase and MgZn2 phase.
2. The high corrosion-resistant zinc-magnesium alloy coated steel sheet according to claim 1, characterized in that, The Zn-Mg eutectic outer layer contains 0.02% to 0.06% Mg by mass, with the balance being Zn and unavoidable impurities; The thickness of the Fe-Zn-Mg ternary alloy inner layer is 1–5 μm.
3. The high corrosion-resistant zinc-magnesium alloy coated steel sheet according to claim 1, characterized in that, The Fe-Zn-Mg ternary alloy inner layer has an equiaxed or fine-grained structure with an average grain size of less than 2 μm, and the Mg content in the inner layer of the ternary alloy increases from the steel matrix side to the eutectic outer layer side along the thickness direction.
4. The high corrosion-resistant zinc-magnesium alloy coated steel sheet according to claim 1, characterized in that, The MgZn2 phase in the Zn-Mg eutectic outer layer is uniformly distributed in the η-Zn matrix in a dispersed granular or short rod-shaped morphology, and the average particle size of the MgZn2 phase does not exceed 3 μm.
5. The high corrosion-resistant zinc-magnesium alloy coated steel sheet according to claim 1, characterized in that, Between the Fe-Zn-Mg ternary alloy inner layer and the steel substrate, there is also a discontinuous Al-containing interface layer. This Al-containing interface layer contains Fe-Al intermetallic compounds and has a thickness of 0.02 to 0.3 μm. Moreover, this Al-containing interface layer is partially penetrated or replaced by the Fe-Zn-Mg ternary alloy inner layer over at least 50% of its area.
6. The high corrosion-resistant zinc-magnesium alloy coated steel sheet according to claim 1, characterized in that, The total thickness of the hot-dip alloy coating is 10-30 μm, and the thickness of the Zn-Mg eutectic outer layer accounts for more than 70% of the total coating thickness.
7. A method for preparing a high corrosion-resistant zinc-magnesium alloy coated steel sheet according to any one of claims 1 to 6, comprising continuously annealing, hot-dip coating, and cooling a cold-rolled steel strip, characterized in that, The hot-dip galvanizing step uses a zinc-based alloy bath, which contains at least Mg and Zn; The immersion temperature is 440–480℃, and the immersion time is 2–6 seconds; After the steel strip is removed from the bath, it is forced to cool to below 400°C at a cooling rate of 10–40°C / s.
8. The preparation method according to claim 7, characterized in that, The forced cooling is implemented in stages: after the steel strip is removed from the bath and purged with an air knife, it is immediately subjected to rapid cooling of 10-40℃ / s. When the surface temperature of the coating drops to 390-400℃, it enters a slow cooling stage with a cooling rate not exceeding 6℃ / s.
9. The preparation method according to claim 7, characterized in that, The zinc-based alloy bath contains 0.02% to 0.20% Mg; the zinc-based alloy bath also contains Al, with an Al content of 0.35% to 0.60%, and an Al / Mg mass ratio of 1.5 to 2.
5.
10. The preparation method according to claim 7, characterized in that, At the immersion temperature, Mg and Al first form Mg-Al intermetallic compound particles in the zinc-based alloy bath, which then adhere to the surface of the steel strip along with the zinc liquid. During the subsequent cooling process, Mg atoms are decomposed and released, participating in the Zn-Mg eutectic reaction and the formation of the Fe-Zn-Mg ternary alloy inner layer. In the initial stage of immersion plating, Al reacts with the steel substrate to form an Al-containing interface barrier layer. In the later stage of immersion plating, this barrier layer is at least partially dissolved in the zinc-based alloy bath, exposing the iron covered by it. The exposed iron reacts with Zn in the zinc-based alloy bath and Mg released from Mg-Al intermetallic compound particles to generate the Fe-Zn-Mg ternary alloy inner layer in situ.